Empati dan Peer Support sebagai Prediktor Perilaku Prososial Siswa SMP: Analisis Perbedaan Berdasarkan Jenis Kelamin - Aulia Nurul Khasanah; Ernest Cety Septyanti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The increasing tendency towards individualistic behavior and low social awareness in adolescents poses challenges for schools in developing prosocial behavior. Although empathy and peer support have been widely studied separately, evidence on their joint contribution to prosocial behavior among junior high school students in Indonesia, as well as their gender differences, remains limited. This study aimed to analyze  empathy and peer support as predictors of students prosocial behavior and to examine gender differences. This studied employed a quantitative correlational design, involving 230 junior high school students selected through purposive sampling. The instruments used included the Interpersonal Reactivity Index scale (α=0.859), the peer support scale (α=0.920), and the prosocial scale (α=0.920). Data was analyzed using multiple linear regression and an independent t-test. The results showed that empathy (β=0.546; p <.001) and peer support (β=0.458; p <.001) contributed significantly to students' prosocial behavior. Both variables together explained 45.3% of the variation in prosocial behavior (R² = 0.453). Furthermore, differences in prosocial behavior were found by gender (t= 3,997; p < .001), with female adolescents exhibiting higher prosocial behavior than male adolescents. This finding indicates that the development of guidance and counseling services should integrate empathy training and strengthen peer support as strategies to enchance students prosocial behavior, while accounting for gender differences.